2-Nitroanilinium bromide - Anitha, R. (International Union of Crystallography, 2011)
The title compound, C(6)H(7)N(2)O(2) (+)·Br(−), is isomorphous with 2-nitroanilinium chloride and contains an characteristic intramolecular N—H⋯O hydrogen bond, forming an S(6) motif. Intermolecular N—H⋯Br hydrogen bonds occur in the crystal structure. Two zigzag chains of C (2) (1)(4) motifs extend along the b-axis direction. These primary chain motifs intersect like a double helix structure, leading to R (6) (3)(12) ring motifs, which are arranged in tandem along the b axis. Hence, hydrophilic layers are generated at z = 1/4 and 3/4, which are sandwiched between alternate hydrophobic layers across z = 0 and 1/2.